COMPARISON OF REGULATION AND LEGAL COMPLIANCE IN ISLAMIC BANKING AMIDST THE TREND OF FINANCIAL GLOBALIZATION - hidayat, Rahmat (IAIN Parepare, 2025)
This article aims to evaluate and compare regulations and legal compliance in Islamic banking across jurisdictions amid the trend of financial globalization. The primary focus of this study is to identify common patterns, research gaps, and policy dynamics that affect the competitiveness and integrity of the global Islamic banking system. The methodology employed is a Systematic Literature Review (SLR), analyzing 30 relevant scholarly articles published between 2010 and 2024. The literature was selected based on strict inclusion and exclusion criteria and was analyzed using narrative and thematic techniques.The findings reveal significant variations in regulatory frameworks among countries, which directly influence the effectiveness of legal compliance and the implementation of Shariah principles. Key discoveries include differences in approaches to legal and Shariah compliance, as well as the challenges of regulatory harmonization under global pressures. Moreover, the roles of international institutions such as AAOIFI and IFSB are assessed as not yet fully effective in promoting global Shariah legal convergence.This study recommends the development of adaptive and collaborative regulatory frameworks among countries, along with stronger synergy between domestic authorities and global institutions to enhance compliance and stability in Islamic banking. The practical implications of these findings are particularly relevant for policymakers, regulators, and Islamic banking practitioners in designing competitive legal frameworks. Theoretically, this article contributes to the literature on legal harmonization and the development of global Islamic financial governance. The study also acknowledges its limitations, particularly regarding its reliance on secondary data and restricted access to certain literature sources, thus opening avenues for further field-based exploration.